2021
DOI: 10.21270/archi.v10i4.4841
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications and antibacterial and antifungal activities of Syzygium cumini (L.) Skeels extracts: a systematized literature review focusing on dental applications

Abstract: Medicinal plants are an important source of curative substances for the treatment of diseases. Investigations are focusing particularly on medicinal plants used to treat affections of the oral cavity. Among these species, there is evidence of potential applications of Syzygium cumini to Dentistry. The objective of this systematized literature review was to synthesize the evidence on the antimicrobial activity of this plant, as well cite some as the traditional uses of its extracts for dental purposes. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The use of medicinal plants can be considered a useful alternative for antimicrobial agents. 61 S. cumini extracts demonstrated remarkable pharmacological and antimicrobial activities. 62 The promising therapeutic activity of S. cumini extracts can be explained by the presence of various groups of bioactive metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of medicinal plants can be considered a useful alternative for antimicrobial agents. 61 S. cumini extracts demonstrated remarkable pharmacological and antimicrobial activities. 62 The promising therapeutic activity of S. cumini extracts can be explained by the presence of various groups of bioactive metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies identified secondary metabolites (phytochemical substances), such as flavonoids, phenolic compounds, saponins, tannins, anthocyanins and terpenes, as antimicrobial compounds. 61 For example, an earlier study displayed the therapeutic benefit of S. cumini extract in treating conditions affecting the oral cavity, including dental caries, periodontitis, dental infections, and yeast infection. 63 S. cumini extracts have also demonstrated a variety of biological activities owing to their anti-inflammatory, antioxidant, and anti-carcinogenic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation